2021
DOI: 10.3390/pathogens10060637
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Nucleocapsid Antibody in COVID-19 Patients in Bangladesh Is not Correlated with Previous Dengue Infection

Abstract: Background: The assessment of antibody responses to severe acute respiratory syndrome coronavirus-2 is potentially confounded by exposures to flaviviruses. The aims of the present research were to determine whether anti-dengue antibodies affect the viral load and the detection of anti-coronavirus nucleocapsid (N)-protein antibodies in coronavirus infectious disease 2019 (COVID-19) in Bangladesh. Methods: Viral RNA was evaluated in swab specimens from 115 COVID-19 patients by real-time reverse transcription pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…Our finding of anti-N-protein IgG positively correlated with anti-S-protein IgG confirms the positive correlation previously reported for unvaccinated natural SARS CoV-2 infection [42] and are consistent with the anti-N-protein IgG levels in Novalisa previously reported among Bangladeshi COVID-19 patients [43]. During the first 21 days POCS, anti-N protein IgG levels are typically higher than the anti-S-protein IgG levels [42].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of anti-N-protein IgG positively correlated with anti-S-protein IgG confirms the positive correlation previously reported for unvaccinated natural SARS CoV-2 infection [42] and are consistent with the anti-N-protein IgG levels in Novalisa previously reported among Bangladeshi COVID-19 patients [43]. During the first 21 days POCS, anti-N protein IgG levels are typically higher than the anti-S-protein IgG levels [42].…”
Section: Discussionsupporting
confidence: 92%
“…Such a finding has been described recently as supporting evidence of non-cross-reactivity between IgG anti-SARS-CoV-2 N Protein and IgG anti-DENV. 34 Our results show an intense transmission for both diseases (DENV and COVID-19), which is not surprising considering the means of spread of these diseases and considering that Loreto region presents some socioeconomics that promotes such transmission: informal employment rates (81.8%), higher monetary poverty levels (28.3%-32.7%), and overcrowding. 28 However, although the relationship between infectious diseases such as DENV and poverty is reported and known, more studies are needed to deepen and clarify the relationship between poverty and DENV and COVID-19 in the city of Iquitos.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study utilized molecular docking and computational analysis to predict a significant surface interaction between DENV envelope (E) monoclonal antibodies and the SARS-CoV-2 receptor-binding domain of the S-protein [ 20 ]. Another study demonstrated that prior exposure to the dengue virus does not affect anti-N antibodies detection in COVID-19 patients using ELISA [ 21 ]. Taking into consideration the targeted antigen of both assays used in this study, the CL-900i targets both the S and N antigens of SARS-CoV-2, with N antigen as the main contributor for the kit according to the manufacturer's “personal communication.” The NovaLisa DENV ELISA targets the whole virus antigens.…”
Section: Discussionmentioning
confidence: 99%